Klimatické změny ve vysoké Arktidě v průběhu holocénu - Prochová, Dominika (Univerzita Karlova, Přírodovědecká fakulta, 2018)
Climatic changes are nowadays frequently discussed subject in the scientific, political and public sphere. For better understanding of their causes, development and possible impacts is one of the basic prerequisites for investigating such anomalies, that have taken place in the past. In natural archives, it is possible to find records not only about their parameters but also about the mentioned impacts - ecosystem changes, earth surface's geomorfological transformartions or the impact on human society. The most studied period of geological time is Holocene. It is about the most recent period and we currently live in its third stage. Thankfully, due to relatively sufficient knowledge of its climatic anomalies we are able to study the climate's contribution with enough complexity to valorize the currently much observed global warming, witch is often connected to human activity. The Arctic is probably the most sensitive place to climate changes on the planet. The warming, that is currently observed around the globe, is there noticeably higher - by the end of the 20th century, the average annual temperature increased twice as fast. The aim of this thesis is, in the form of literary research, to describe and examinatie the climate development in high Arctic areas, potencially the most sensitive. Klimatické změny jsou v současnosti velice často probíraným tématem ve vědecké, politické i veřejné sféře. Abychom mohli lépe porozumět jejich příčinám, průběhu, vývoji a možným dopadům, je jedním ze základních předpokladů zkoumat obdobné změny, které probíhaly v minulosti. V přírodních archivech je možné nalézt nejen záznamy o jejich parametrech, ale i o zmiňovaných dopadech - změnách ekosystémů, geomorfologických změnách zemského povrchu, či vlivu na lidskou společnost. Nejprostudovanějším obdobím geologického času je holocén. Jde o období nejmladší a žijeme v jeho třetí etapě. Díky relativně dobré znalosti jeho klimatických anomálií můžeme studovat roli klimatu velmi komplexně a zhodnotit tak i v současnosti pozorované ...